Arquitectura Empresarial de la Agencia Nacional de Infraestructura - ANI - Varón G., Yenny Paola; Castaño Fernandez, Sebastian (Escuela Colombiana de Ingeniería Julio Garavito, 2017)
This document contains the description of the work carried out, that is, the documentation of the Business Architecture of the National Infrastructure Agency, focused on the IT Architecture Reference Framework of Colombia proposed by the Ministry of Information Technologies and Communications - MinTIC. The repository of the Architecture is hosted on servers belonging to the National Infrastructure Agency and the information is confidential.

Este documento contiene la descripción del trabajo realizado, es decir la documentación de la Arquitectura Empresarial de la Agencia Nacional de Infraestructura, enfocada en el Marco de Referencia de Arquitectura de TI de Colombia propuesta por el Ministerio de Tecnologías de Información y las Comunicaciones – MinTIC. El repositorio de la Arquitectura se encuentra alojado en servidores que pertenecen a la Agencia Nacional de Infraestructura y la información es confidencial.
Keywords: Arquitectura empresarial; Tecnología de la información; Business architecture; Information technology